Chemical syntheses and salient features of azulene-containing homo- and copolymers - Shetti, Vijayendra S. (Beilstein Journal of Organic Chemistry, 2021)
Azulene is a non-alternant, aromatic hydrocarbon with many exciting characteristics such as having a dipole moment, bright color, stimuli responsiveness, anti-Kasha photophysics, and a small HOMO–LUMO gap when compared to its isomer, naphthalene. These properties make azulene-containing polymers an intriguing entity in the field of functional polymers, especially for organic electronic applications like organic field-effect transistors (OFET) and photovoltaic (PV) cells. Since azulene has a fused five and seven-membered ring structure, it can be incorporated onto the polymer backbone through either of these rings or by involving both the rings. These azulene-connection patterns can influence the properties of the resulting polymers and the chemical synthesis in comparison to the electrochemical synthesis can be advantageous in obtaining desired patterns of substitution. Hence, this review article presents a comprehensive overview of the developments that have taken place in the last three decades in the field of chemical syntheses of azulene-containing homo- and copolymers, including brief descriptions of their key properties.
Keywords: azulene; chemical synthesis; copolymer; non-alternant hydrocarbon; organic electronics; polyazulene

(untitled) - Gordon, M. (Chem. Rev., 1952)

(untitled) - Hafner, K. (Justus Liebigs Ann. Chem., 1957)

(untitled) - Lemal, D. M.; Goldman, G. D. (J. Chem. Educ., 1988)

(untitled) - Salter, C.; Foresman, J. B. (J. Chem. Educ., 1998)

(untitled) - Liu, R. S. H. (J. Chem. Educ., 2002)

(untitled) - Demchenko, A. P.; Tomin, V. I.; Chou, P.-T. (Chem. Rev., 2017)

(untitled) - Xin, H.; Gao, X. (ChemPlusChem, 2017)

(untitled) - Dong, J.-X.; Zhang, H.-L. (Chin. Chem. Lett., 2016)

(untitled) - Yamaguchi, Y.; Ogawa, K.; Nakayama, K.-i.; Ohba, Y.; Katagiri, H. (J. Am. Chem. Soc., 2013)

(untitled) - Wang, F.; Lin, T. T.; He, C.; Chi, H.; Tang, T.; Lai, Y.-H. (J. Mater. Chem., 2012)

(untitled) - Yamaguchi, Y.; Maruya, Y.; Katagiri, H.; Nakayama, K.-i.; Ohba, Y. (Org. Lett., 2012)

(untitled) - Amir, E.; Amir, R. J.; Campos, L. M.; Hawker, C. J. (J. Am. Chem. Soc., 2011)

(untitled) - Murai, M.; Ku, S.-Y.; Treat, N. D.; Robb, M. J.; Chabinyc, M. L.; Hawker, C. J. (Chem. Sci., 2014)

(untitled) - Xin, H.; Hou, B.; Gao, X. (Acc. Chem. Res., 2021)

(untitled) - Huang, J.; Huang, S.; Zhao, Y.; Feng, B.; Jiang, K.; Sun, S.; Ke, C.; Kymakis, E.; Zhuang, X. (Small Methods, 2020)

(untitled) - Zeng, H. N.; Png, Z. M.; Xu, J. (Chem. – Asian J., 2020)

(untitled) - Tourillon, G.; Garnier, F. (J. Electroanal. Chem. Interfacial Electrochem., 1982)

(untitled) - Neoh, K. G.; Kang, E. T.; Tan, T. C. (Polym. Bull., 1988)

(untitled) - Kihara, N.; Nakayama, H.; Fukutomi, T. (Macromolecules, 1997)

(untitled) - Wang, F.; Lai, Y.-H.; Kocherginsky, N. M.; Kosteski, Y. Y. (Org. Lett., 2003)

(untitled) - Tang, T.; Kyaw, A. K. K.; Zhu, Q.; Xu, J. (Chem. Commun., 2020)

(untitled) - Murai, M.; Amir, E.; Amir, R. J.; Hawker, C. J. (Chem. Sci., 2012)

(untitled) - Dutta, S.; Lakshmi, S.; Pati, S. K. (Bull. Mater. Sci., 2008)

(untitled) - Dias, J. R. (J. Phys. Org. Chem., 2007)

(untitled) - Koch, M.; Blacque, O.; Venkatesan, K. (J. Mater. Chem. C, 2013)

(untitled) - Hou, I. C.-Y.; Shetti, V.; Huang, S.-L.; Liu, K.-L.; Chao, C.-Y.; Lin, S.-C.; Lin, Y.-J.; Chen, L.-Y.; Luh, T.-Y. (Org. Chem. Front., 2017)

(untitled) - Wang, F.; Lai, Y.-H. (Macromolecules, 2003)

(untitled) - Wang, F.; Lai, Y.-H.; Han, M.-Y. (Macromolecules, 2004)

(untitled) - Tang, T.; Ding, G.; Lin, T.; Chi, H.; Liu, C.; Lu, X.; Wang, F.; He, C. (Macromol. Rapid Commun., 2013)

(untitled) - Yamamoto, T.; Morita, A.; Miyazaki, Y.; Maruyama, T.; Wakayama, H.; Zhou, Z.-h.; Nakamura, Y.; Kanbara, T.; Sasaki, S.; Kubota, K. (Macromolecules, 1992)

(untitled) - Ruiz, J. P.; Dharia, J. R.; Reynolds, J. R.; Buckley, L. J. (Macromolecules, 1992)

(untitled) - Wang, F.; Lai, Y.-H.; Han, M. Y. (Org. Lett., 2003)

(untitled) - Tang, T.; Lin, T.; Wang, F.; He, C. (Polym. Chem., 2014)

(untitled) - Tang, T.; Lin, T.; Wang, F.; He, C. (J. Phys. Chem. B, 2015)

(untitled) - Tsurui, K.; Murai, M.; Ku, S.-Y.; Hawker, C. J.; Robb, M. J. (Adv. Funct. Mater., 2014)

(untitled) - Yao, J.; Cai, Z.; Liu, Z.; Yu, C.; Luo, H.; Yang, Y.; Yang, S.; Zhang, G.; Zhang, D. (Macromolecules, 2015)

(untitled) - Xin, H.; Ge, C.; Jiao, X.; Yang, X.; Rundel, K.; McNeill, C. R.; Gao, X. (Angew. Chem., Int. Ed., 2018)

(untitled) - Mao Png, Z.; Xu, J. (Chem. – Asian J., 2020)

(untitled) - Png, Z. M.; Tam, T. L. D.; Xu, J. (Org. Lett., 2020)

(untitled) - Wang, X.; Ng, J. K.-P.; Jia, P.; Lin, T.; Cho, C. M.; Xu, J.; Lu, X.; He, C. (Macromolecules, 2009)

(untitled) - Gao, H.; Ge, C.; Hou, B.; Xin, H.; Gao, X. (ACS Macro Lett., 2019)

(untitled) - Lim, S. Z. H.; Neo, W. T.; Cho, C. M.; Wang, X.; Tan, A. Y. X.; Chan, H. S. O.; Xu, J. (Aust. J. Chem., 2013)

(untitled) - Umeyama, T.; Watanabe, Y.; Miyata, T.; Imahori, H. (Chem. Lett., 2015)

(untitled) - Ding, G.; Cho, C. M.; Chen, C.; Zhou, D.; Wang, X.; Tan, A. Y. X.; Xu, J.; Lu, X. (Org. Electron., 2013)

(untitled) - Puodziukynaite, E.; Wang, H.-W.; Lawrence, J.; Wise, A. J.; Russell, T. P.; Barnes, M. D.; Emrick, T. (J. Am. Chem. Soc., 2014)

(untitled) - Kolb, H. C.; Finn, M. G.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2001)